Porosity of Convex Nowhere Dense Subsets of Normed Linear Spaces. (10th December 2009) - Strobin, Filip
Abstract : This paper is devoted to the following question: how to characterize convex nowhere dense subsets of normed linear spaces in terms of porosity? The motivation for this study originates from papers of V. Olevskii and L. Zajíček, where it is shown that convex nowhere dense subsets of normed linear spaces are porous in some strong senses.